Analisis Pengaruh Aspek Keperilakuan Terhadap Sistem Informasi Akuntansi - Sulastri, Emilda (Disclosure: Journal of Accounting and Finance, 2021)
The purpose of this study was to analyze the behavioral aspects of the accounting information system at Pt. Mandiri Tunas Finance Bengkulu branch is a service company engaged in banking, especially in the automotive financing sector.The purpose of this study was to analyze the behavioral aspects of the accounting information system at Pt. Mandiri Tunas Finance Bengkulu branch is a service company engaged in banking, especially in the automotive financing sector.From hypothesis testing, it is found that behavioral aspects (behavior, motivation, perception) have no significant effect on the accounting information system run by the company.In this study, attitudes have no significant effect on the accounting information system because employees do their work in accordance with applicable rules so that behavior is classified as good. Motivation also has no significant effect on accounting information systems. This shows that the company''s management has motivated employees in the form of rewards or moral support. Perception also has no significant effect on the existing accounting information system at Pt. Mandiri Tunas Finance Bengkulu branch. This is because the way of thinking, tasks and work done by employees is good.